A generous ontology: Identity as a process of intersubjective discovery – An African theological contribution - Forster, Dion Angus (HTS teologiese studies, 2010)
The answer to the question ‘who am I?’ is of fundamental importance to being human. Answers to this question have traditionally been sought from various disciplines and sources, which include empirical sources, such as biology and sociology, and phenomenological sources, such as psychology and religion. Although the approaches are varied, they have the notion of foundational truth, whether from an objective or subjective perspective, in common. The question of human identity that is the subject of this paper is germinated from the title of a book by WITS academic, Ivor Chipkin, entitled, Do South Africans exist? Nationalism, democracy and the identity of ‘the people’ (2007). This paper does not discuss Chipkin’s thoughts on nationalism and democracy; however, it considered the matter of human identity that is raised by his question. The approach taken by this paper on the notion of identity was significantly influenced by Brian McLaren’s postmodernist approach to Christian doctrine as outlined in his book A generous orthodoxy (2004) – a term coined by Yale Theologian, Hans Frei. The inadequacies of traditional approaches to human identity and consciousness that are based upon ‘foundational knowledge’ were thus considered. Both subjective and objective approaches to identity were touched upon, showing the weaknesses of these approaches in dealing with the complex nature of true human identity. The paper then presented an integrative framework for individual consciousness that is not static or ultimately quantifiable, but rather formulated in the process of mutual discovery that arises from a shared journey. The approach presented here drew strongly upon the groundbreaking work of Ken Wilber and Eugene de Quincey and related their ontological systems to the intersubjective approach to identity that can be found in the African philosophy and theology of ‘ubuntu’. This paper focused on how the ethics and theology of this indigenous knowledge system can contribute toward overcoming the impasse of validating individual identity in contemporary academic debates on human consciousness.